2023
DOI: 10.53854/liim-3101-2
|View full text |Cite
|
Sign up to set email alerts
|

Invasive cryptococcal disease in COVID-19: systematic review of the literature and analysis

Abstract: During the Coronavirus Disease 2019 (COVID-19) pandemic, an increasing number of fungal infections associated with SARS-CoV-2 infection have been reported. Among them, cryptococcosis could be a lifethreatening disease. We performed a Systematic Review (PRISMA Statement) of cryptococcosis and CO-VID-19 co-infection, case report/series were included: a total of 34 cases were found, then we added our case report. We collected patients' data and performed a statistical analysis comparing two groups of patients sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Previously, ICU admission and MV were reported as important risk factors in literature reviews on the subject. 50 , 72 Our findings were similar for both variables; in addition to these, we also found that secondary infections/co-infections (the majority being bacterial infections) turned out to be a risk factor associated with mortality. It should be noted that it was difficult to distinguish between both according to the information provided by the papers, thus for the patients in the present review it would be an additional infection to cryptococcosis and COVID-19 and could be either a co-infection or secondary infection.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Previously, ICU admission and MV were reported as important risk factors in literature reviews on the subject. 50 , 72 Our findings were similar for both variables; in addition to these, we also found that secondary infections/co-infections (the majority being bacterial infections) turned out to be a risk factor associated with mortality. It should be noted that it was difficult to distinguish between both according to the information provided by the papers, thus for the patients in the present review it would be an additional infection to cryptococcosis and COVID-19 and could be either a co-infection or secondary infection.…”
Section: Discussionsupporting
confidence: 81%
“…Overall, cryptococcosis in COVID-19 patients is not as frequent compared to other fungal infections such as mucormycosis 70 and aspergillosis, 71 widely reported in the literature, in COVID-19 patients, although it can still be life-threatening in light of the high mortality, ranging between 50% and 65%. 23 , 50 , 72 , 73 Our analysis showed that the majority of patients were men and around 60 years of age, and in addition, it was determined that both male sex and age are risk factors associated with mortality. The male sex is related to the incidence, severity, and mortality of COVID-19.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations